The Technical Feasibility of Unilateral Biportal Endoscopic Decompression for The Unpredicted Complication Following Minimally Invasive Transforaminal Lumbar Interbody Fusion: Case Report - Kwang-Ryeol Kim; Jeong-Yoon Park (Neurospine, 2020)
Minimally invasive techniques for transforaminal lumbar interbody fusion (MIS-TLIF) are advantageous because they allow for sufficient surgical exposure and fewer complications through a smaller incision than conventional TLIF. It could be difficult to maintain minimally invasive spine surgery following the unexpected complications after MIS-TLIF. Because MIS-TLIF is usually done via a paramedian small incision with posterior fusion using screws and rods, visualization of the surgical field is limited, and it is difficult to directly assess the neural structure without removing instrumentation. Unilateral biportal endoscopic decompression (UBE) is a rapidly growing surgical method using two 1-cm incisions that are 2 to 3 cm apart. We would like to suggest UBE as an option for immediate reoperation after MIS-TLIF because it has the advantages of targeting pathologic regions and a wide field of visualization through small wounds. The operation is independent of the existing incision from MIS-TLIF, enabling immediate revision surgery without the removal of the screws and rods. UBE has the advantages of targeting specific surgical regions and providing a wide visualization of the operation field through small incisions. UBE can be very useful for discectomy or decompression surgery as well as in immediate reoperation after MIS-TLIF.